1997
DOI: 10.1105/tpc.9.2.237
|View full text |Cite
|
Sign up to set email alerts
|

The self-incompatibility (S) haplotypes of Brassica contain highly divergent and rearranged sequences of ancient origin.

Abstract: In Brassica, the recognition of self-related pollen by the stigma is controlled by the highly polymorphic S locus that encodes several linked and coadapted genes and can span several hundred kilobases. We used pulsed-field gel electrophoresis to analyze the structure of different S haplotypes. We show that the S, and S,3 haplotypes of Brassica oleracea contain extensive sequence divergence and rearrangement relative to each other. In contrast, haplotypic configuration is more conserved between 8. oleracea S,3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
47
1

Year Published

1998
1998
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(48 citation statements)
references
References 43 publications
0
47
1
Order By: Relevance
“…Note that rearranged gene order and fractured homology often are associated with complex loci and are thought to reduce the frequency of recombination within coadapted gene complexes (Ferris and Goodenough, 1994). Similarly, structural heteromorphism at the S locus might serve to maintain the tight association of the SI specificity genes over time (Boyes et al, 1997;Casselman et al, 2000).An unexpected result of our study was the finding that the S locus occupies different chromosomal locations in Brassica and Arabidopsis spp. In Brassica, the S locus is located in a region that is syntenous with an ETR1-linked chromosomal segment of A. thaliana chromosome I (Conner et al, 1998), whereas in A. lyrata, the S locus maps to a region that corresponds to contig fragments 54 to 55 of A. thaliana chromosome IV.…”
contrasting
confidence: 50%
See 1 more Smart Citation
“…Note that rearranged gene order and fractured homology often are associated with complex loci and are thought to reduce the frequency of recombination within coadapted gene complexes (Ferris and Goodenough, 1994). Similarly, structural heteromorphism at the S locus might serve to maintain the tight association of the SI specificity genes over time (Boyes et al, 1997;Casselman et al, 2000).An unexpected result of our study was the finding that the S locus occupies different chromosomal locations in Brassica and Arabidopsis spp. In Brassica, the S locus is located in a region that is syntenous with an ETR1-linked chromosomal segment of A. thaliana chromosome I (Conner et al, 1998), whereas in A. lyrata, the S locus maps to a region that corresponds to contig fragments 54 to 55 of A. thaliana chromosome IV.…”
contrasting
confidence: 50%
“…Class I consists of S haplotypes that are placed high in the dominance series and that determine a robust SI response; class II consists of S haplotypes that are recessive to class I haplotypes in pollen and that determine a relatively leaky SI response (Chen and Nasrallah, 1990;Kusaba et al, 1997). Class I and class II SRK alleles diverge by Ͼ 30%, whereas class I and class II SCR alleles are so diverged from one another (Schopfer et al, 1999) that the high number of available class I SCR sequences has not allowed the isolation of class II SCR alleles.Comparative mapping of different S haplotypes has demonstrated that they vary not only in the sequence of their SI genes but also in the order, relative orientation, and spacing of these genes (Boyes and Nasrallah, 1993;Boyes et al, 1997;Cui et al, 1999;Nasrallah, 2000;Takayama et al, 2000). This structural heteromorphism and the sequence polymorphism of SI genes exhibit trans -specific variation (Dwyer et al, 1991;Kusaba et al, 1997;Schopfer et al, 1999; Uyenoyama, 2000).…”
mentioning
confidence: 99%
“…Sequence analysis of the S c haplotype region revealed that the region is rich in retrotransposon-like sequences, which may have been causal to the region being heteromorphic. These findings indicate that the almond S locus has been subjected to repeated rearrangements, deletions, and insertions, like the S locus of Brassicaceae (Boyes et al, 1997;Casselman et al, 2000;Kusaba et al, 2001). The structural heteromorphism is a distinctive feature of loci consisting of coadapted gene complexes in different genetic systems (Ferris and Goodenough, 1994;Brown and Casselton, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…This has suggested that functional self-incompatibility requires alleles from the two loci to be similar and that recombination between the two loci is suppressed to maintain this matching (Stein et al, 1991). High sequence divergence in the region between the loci (Boyes et al, 1997) and near Petunia inflata S-loci (Coleman & Kao, 1992) support rarity of recombinational exchange, but divergence could be due to relaxed selection in these flanking regions. Sequence differences are not only a feature of S-loci, but are also found in maize intergenic regions (Sanmiguel et al, 1997).…”
Section: Linkage Disequilibrium and Recombination In The Slg-srk Regionmentioning
confidence: 99%